Experimental study of zooplankton behaviour - Ho, Wei How (Nanyang Technological University, 2023)
Daphnia are small planktonic crustaceans that are commonly found in lakes and ponds. They are commonly used as experimental organism to investigate the effects of external stimuli on the aquamarine ecosystem. There has been a myriad of studies showcasing the effects of different stimuli and its impact on Daphnia mortality, and these studies tend to be over a long period of time or use complicated parameters. However, Daphnia mortality may not be sufficient and accurate to appraise the stimulus’ long-term consequences on Daphnia and its water ecosystem. As such, this project will focus on stimuli effect on swimming behaviour with quantitative parameters, allowing us to better study Daphnia behaviour as compared to a binary endpoint of mortality. Daphnia will be experimented with common waterbody microplastic pollutants such as Nylon12 (PA12), Polyethylene (PE), and Acetamiprid (pesticide) over various concentrations. In addition, daphnia of varying sizes will be experimented with. The results show that, Nylon 12 acts as a stimulus for Daphnia Magna at all experimented concentrations, Polyethylene too acts as a stimulus for Daphnia Magna but only up till concentrations of about 150 mg/L before inhibition. Adversely, Acetamiprid is not a stimulus for Daphnia Magna, as it generally decreases swimming activity, and should be noted as hazardous for Daphnia. Daphnia size only affects swimming behaviour at the start of the experiment. After the experiments are conducted and data collected, it can be concluded that the 2 microplastics are a stimulus to Daphnia and its ecosystem, and Acetamiprid is generally harmful. Daphnia size affects initial swimming behaviour but has no observable effect on swimming behaviour otherwise.